Quality of patient‐reported outcome reporting across cancer randomized controlled trials according to the CONSORT patient‐reported outcome extension: A pooled analysis of 557 trials. Issue 18 (16th June 2015) - Efficace, Fabio; Fayers, Peter; Pusic, Andrea; Cemal, Yeliz; Yanagawa, Jane; Jacobs, Marc; la Sala, Andrea; Cafaro, Valentina; Whale, Katie; Rees, Jonathan; Blazeby, Jane; for the European Organization for Research and Treatment of Cancer Quality‐of‐Life Group (Patient‐Reported Outcome Measurements Over Time in Oncology Registry)
<x xml:space="preserve">Abstract</x> BACKGROUND The main objectives of this study were to identify the number of randomized controlled trials (RCTs) including a patient‐reported outcome (PRO) endpoint across a wide range of cancer specialties and to evaluate the completeness of PRO reporting according to the Consolidated Standards of Reporting Trials (CONSORT) PRO extension. METHODS RCTs with a PRO endpoint that had been performed across several cancer specialties and published between 2004 and 2013 were considered. Studies were evaluated on the basis of previously defined criteria, including the CONSORT PRO extension and the Cochrane Collaboration's tool for assessing the risk of bias of RCTs. Analyses were also conducted by the type of PRO endpoint (primary vs secondary) and by the cancer disease site. RESULTS A total of 56, 696 potentially eligible records were scrutinized, and 557 RCTs with a PRO evaluation, enrolling 254, 677 patients overall, were identified. PROs were most frequently used in RCTs of breast (n = 123), lung (n = 85), and colorectal cancer (n = 66). Overall, PROs were secondary endpoints in 421 RCTs (76%). Four of 6 evaluated CONSORT PRO items were documented in less than 50% of the RCTs. The level of reporting was higher in RCTs with a PRO as a primary endpoint. The presence of a supplementary report was the only statistically significant factor associated with greater completeness of reporting for both RCTs with PROs as primary endpoints (β = .19, P = .001) and RCTs with PROs as secondary endpoints (β = .30, P < .001). CONCLUSIONS Implementation of the CONSORT PRO extension is equally important across all cancer specialties. Its use can also contribute to revealing the robust PRO design of some studies, which might be obscured by poor outcome reporting. Cancer 2015;121:3335–3342. © 2015 American Cancer Society.